Analysis and experiment of stress concentration in penetration fuze buffer materials under stress wave incursion - Zhang, An; Liu, Peng; Zhang, He (Frontiers in Physics, 2024)
To enhance the impact resistance of penetration fuze, this paper investigates the response of fuze buffer materials to stress waves and develops a model for stress wave transmission inside the fuze. The stress concentration impacts of different cell structures of Imitation Bamboo Type Penetration Fuze Buffer Protection Structure (IBS) under stress wave action are compared and analyzed. The paper elucidates the impact of different cell parameters on stress concentration impacts, establishes nonlinear fitting functions of Stress Concentration Factor (SCF) and cell parameters, and solves the prediction error. Based on the wave function expansion method, an expression for Dynamic Stress Concentration Factor (DSCF) when stress waves interact with the potting material is derived, and numerical results of DSCF around bubbles under different physical parameters are provided. Finally, dynamic impact tests are conducted on the combined buffer scheme of penetration fuze. Impact test results show that, under an initial velocity impact of 50 m/s, the overload peak attenuation rate is 39.42%, and under an initial velocity impact of 70 m/s, the overload peak attenuation rate is 32.87%. IBS can effectively protect the electronic components inside the fuze.